The influence of iodide on glass transition temperature of high‐pressure nuclear waste glasses. Issue 3 (22nd November 2020) - Jolivet, Valentin; Morizet, Yann; Hamon, Jonathan; Paris, Michael; Suzuki‐Muresan, Tomo
Abstract: The glass transition temperature (Tg ) is a key parameter to investigate for application in nuclear waste immobilization in borosilicate glasses. Tg for several glasses containing iodine (I) has been measured in order to determine the I effect on Tg . Two series of glass composition (ISG and NH) containing up to 2.5 mol% I and synthesized under high pressure (0.5 to 1.5 GPa) have been investigated using differential scanning calorimetry (DSC). The I local environment in glasses has been determined using X‐ray photoelectron spectroscopy and revealed that I is dissolved under its iodide form (I − ). Results show that Tg is decreased with the I addition in the glass in agreement with previous results. We also observed that this Tg decrease is a strong function of glass composition. For NH, 2.5 mol% I induces a decrease of 24°C in Tg, whereas for ISG, 1.2 mol% decreases the Tg by 64°C. We interpret this difference as the result of the I dissolution mechanism and its effect on the polymerization of the boron network. The I dissolution in ISG is accompanied by a depolymerization of the boron network, whereas it is the opposite in NH. Although ISG corresponds to a standardized glass, for the particular case of I immobilization it appears less adequate than NH considering that the decrease in Tg for NH is small in comparison to ISG.